Analysis of Student Errors in Solving SPLDV Problems based on Newman's theory - Tika Septia; Izzatun Nazilah (Noumerico: Journal of Technology in Mathematics Education, 2023)
The purpose of this study was to describe the types of errors made by Class VIII students when solving SPLDV questions based on Newman's theory. This qualitative research aims to provide descriptive information about individuals or observed behavior in the form of written or spoken words. Written tests and interviews were used to collect data. The test was carried out on all 25 Class VIII students, and then 3 of the 25 students were selected as research subjects. Data were analyzed by reducing information, presenting information, and drawing conclusions. The results of the work of individual testers were analyzed for the types of errors using the Newman analysis method. The factors that led to student errors were then explained in the interviews. Based on the study results, it can be concluded that the errors made by students in the SPLDV questions are as follows: 1) Failure to understand the problem, including not recording what is known and what is not in the duration of the task. Ask when in trouble. 2) Conversion errors, including misunderstanding of the billing method used. 3) Commanding process failure involves failing to continue to complete the process. 4) Error in writing HP, including not writing down HP. Student errors occur when students are not careful when solving problems, are too busy, or do not practice narrative tasks. 3) Commanding process failure involves failing to continue to complete the process. 4) Error in writing HP, including not writing down HP. Student errors occur when students are not careful when solving problems, are too busy, or do not practice narrative tasks. 3) Commanding process failure involves failing to continue to complete the process. 4) Error in writing HP, including not writing down HP. Student errors occur when students are not careful when solving problems, are too busy, or do not practice narrative tasks